Effects of alcohol on sleep and nocturnal heart rate: Relationships to intoxication and morning‐after effects. (1st September 2022) - Pabon, Elisa; Greenlund, Ian M.; Carter, Jason R.; de Wit, Harriet
Abstract: Background: Alcohol consumption produces feelings of well‐being and stimulation, but also impairs psychomotor performance, disturbs cardiovascular function and sleep, and can disrupt next‐day mood and behavior. A deeper understanding of how the acute effects of alcohol relate to its sleep and morning‐after effects is needed to minimize harm resulting from its use. This study examined relationships between the effects of a high dose of alcohol on subjective and psychomotor measures, nocturnal heart rate, sleep quality, and morning‐after mood and behavior. We hypothesized that alcohol would produce disturbances in cardiovascular and sleep regulation during the night, which would predict morning‐after mood and behavioral performance. Methods: Thirty‐one men and women participated in two overnight laboratory visits during which they consumed either alcohol (1.0 g/kg for men, 0.85 g/kg for women) or placebo (randomized, crossover design). They consumed the beverage from 8 to 9 pm, and remained in the laboratory overnight for polysomnographic sleep recording. Subjective and behavioral measures were obtained during consumption and at 7–8 am the morning after. Results: Alcohol increased both negative and positive arousal, urge to drink and sedation, and it impaired performance on behavioral tasks. During sleep, alcohol produced expected tachycardia and detriments in sleep quality including decreased total sleep time, sleep efficiency, and altered sleep architecture. Only modest effects on mood or performance were detected the following morning. The acute sedative‐like effects of alcohol were related to increases in N2 sleep, but not to other disruptions in sleep or nocturnal heart rate, and neither sleep impairments nor nocturnal heart rate were related to mood or task performance the morning after. Conclusions: The effects of alcohol on sleep and nocturnal heart rate were not strongly related to either its acute or morning‐after effects. These findings do not provide strong support for the idea that alcohol‐induced sleep disruptions underlie morning‐after effects. Abstract : Alcohol produces arousal and stimulation, but also impairs psychomotor performance, disturbs cardiovascular function and sleep, and disrupts next‐day mood and behavior. In a sample of healthy adult alcohol drinkers, we examined relationships between the acute effects of alcohol, nocturnal heart rate, sleep quality and morning‐after mood and behavior. During sleep, alcohol increased heart rate and decreased sleep quality, yet modest morning‐after effects were detected. Neither sleep quality nor nocturnal heart rate were related to either acute or morning‐after effects of alcohol.